Return to Virgin River - Carr, Robyn (Waterville, ME : Wheeler Publishing, a part of Gale, a Cengage Company, 2020)
"Kaylee Sloan$1 (Bs home in Southern California is full of wonderful memories of the woman who raised her. But the memories are prolonging her grief over her mother$1 (Bs recent death. A successful author, Kaylee hoped she could pour herself into her work. Instead she has terrible writer$1 (Bs block and a looming deadline. Determined to escape distractions and avoid the holiday season, Kaylee borrows a cabin in Virgin River. She knows the isolation will help her writing, and as she drives north through the mountains and the majestic redwoods, she immediately feels inspired. Until she arrives at a building that has just gone up in flames. Devastated, she heads to Jack$1 (Bs Bar to plan her next steps."--s
Keywords: Small cities -- Fiction; Man-woman relationships -- Fiction; Women authors -- Fiction; California, Northern -- Fiction; Virgin River (California) -- Fiction; Large type books; Romance fiction; Christmas fiction